Change in the Global LNG Market and the United States Export Potential (Economic and Political Thought, 2012)
As a result of the dynamic growth of the LNG market, natural gas isbecoming the pillar that helps to build global energy security. Additionally,there are also other important elements such as the global attempts to protectthe natural environment, the consequences of the nuclear catastrophe inJapan, still low price competitiveness of renewable energy sources, theeconomic crisis forcing most economies in the world cut costs, and – finally– the development of new technologies that make it possible to extract gasfrom unconventional sources. The latest factor, originating in the UnitedStates, created opportunities for that country to join the group of global LNGexporters.